Transformasi Sosial Desa Ngampon Melalui KKN: Integrasi RPS, TPA, Seni Tari, dan Posyandu sebagai Pilar Pemberdayaan - Nashrul mu'minin; Muhammad Alfian Mirza; Muhammad Ishak Rumwokas; Oktavianus Mandela Agom; Angela Febriani Saputri; Maria Febiola Jesika; Mariana Oni Bere; Nur Hilmiyati; Yuyun Sulastri; Rafika Arjiani; Toto Hermawan (Gemi: Jurnal Penelitian dan Pengabdian, 2026)
The Community Service Program (KKN) in Ngampon Village was initiated to strengthen community empowerment based on education, health, environment, and culture. This program aimed to promote social transformation through integrating Waste Sorting House (RPS) activities, TPA teaching, dance training, and participation in the Integrated Health Post (Posyandu). The methods applied included field surveys, participatory observation, and collaborative practice with residents. Ten KKN students contributed to building the RPS foundation as an initial step toward integrated waste management, trained children in dance for community performances, taught TPA at Al Hidayah Mosque, and supported health services for toddlers and the elderly. The results indicated increased community participation, greater children’s involvement in educational programs, and stronger awareness of health and environmental issues. This program demonstrates that collaboration between students and the community can serve as a sustainable pillar of village social transformation and participatory development initiatives.